Paradoxical Effect of Non-Physiological Shear Stress on Platelets and von Willebrand factor - Chen, Zengsheng (Artif Organs, 2015)
Blood can become hypercoagulable by shear-induced platelet activation and generation of microparticles. It has been reported that non-physiological shear stress (NPSS) could induce shedding of platelet receptor glycoprotein (GP) Ibα, which may result in an opposite effect to hemostasis. The aim of this study was to investigate the influence of the NPSS on platelets and von Willebrand factor (vWF). Human blood was exposed to two levels of NPSS (25Pa, 125Pa) with an exposure time of 0.5 sec., generated by using a novel blood shearing device. Platelet activation (P-selectin expression, GPIIb/IIIa activation and generation of microparticles) and shedding of three platelet receptors (GPIbα, GPVI, GPIIb/IIIa) in sheared blood were quantified using flow cytometry. Aggregation capacity of sheared blood induced by ristocetin and collagen was evaluated using an aggregometer. Shear-induced vWF damage was characterized with western blotting. Consistent with the published data, the NPSS caused significantly more platelets to become activated with increasing NPSS level. Meanwhile, the NPSS induced the shedding of platelet receptors. The loss of the platelet receptors increased with increasing NPSS level. The aggregation capacity of sheared blood induced by ristocetin and collagen decreased. There was a loss of high molecular weight multimers (HMWM) of vWF in sheared blood. These results suggest that the NPSS induced a paradoxical effect. More activated platelets increase the risk of thrombosis while the reduction in platelet receptors and the loss of HMWM-vWF increased the propensity of bleeding. The finding might provide a new perspective to understand thrombosis and acquired bleeding disorder in patients supported with blood contacting medical devices.